Peningkatan Kapasitas Kelompok Budidaya Ikan Melalui Pelatihan Formulasi Pakan Program CSR PT. Pertamina Patra Niaga Fuel Terminal Lomanis - Lestari, Eva Piniji; Hutama, Andy Yudha; Rasyid, Manshur; Puspitasari, Ita (Beujroh : Jurnal Pemberdayaan dan Pengabdian pada Masyarakat, 2025)
The aquaculture sector holds a strategic role in safeguarding food security, generating employment, and improving community welfare. Nevertheless, fish farmers continue to face critical challenges, particularly the high cost of feed—reaching 60–70% of total production expenses—and limited technical expertise in formulating high-quality feed. In response, PT Pertamina Patra Niaga Fuel Terminal (FT) Lomanis implemented a Corporate Social Responsibility (CSR) initiative aimed at strengthening the capacity of farmer groups through specialized training in independent feed formulation. This program was delivered through a participatory approach that combined technology demonstrations with hands-on practice, engaging the Fish Farmers Group (Pokdakan) Pur 123 Indah Jaya in Sidamukti Village. The training significantly enhanced participants’ knowledge and skills in formulating feed using locally available raw materials with balanced nutritional content, while also equipping them with the ability to operate the extruder machine effectively and independently. In addition to producing more affordable and higher-quality feed, the program fostered greater group self-reliance, reduced dependence on commercial feed, and promoted sustainable development. These outcomes reflect the essence of CSR as guided by the triple bottom line framework, which emphasizes economic, social, and environmental sustainability.